Contribution to the knowledge of gasteroid fungi (Agaricomyetes, Basidiomycota) from the State of São Paulo, Brazil - Fernandes, Natiele Stephanie Rubio (2021)
The knowledge about gasteroid fungi in Brazil have increased considerably during the last two decades. However, there are still areas in the country where no species reported, and on the other hand, there are species that were reported only from a few localities. About 70 species of gasteroid fungi are reported from the State of São Paulo (Southeastern Brazil), but this number may be increased with more collections and studies. The aim of this article is to report for the first time the occurrence of nine gasteroid species from São Paulo: Calvatia fragilis, C. guzmanii, Cyathus julietae, Geastrum argentinum, G. minimum, G. violaceum, Phallus glutinolens, Scleroderma areolatum and Vascellum pampeanum. The latter is also a new report from Brazil. Moreover, additional comments are provided for the species Abrachium floriforme, Arachnion album and Phallus rubicundus.